Tradisi Menabur Beras Kuning dalam Prosesi Pernikahan - Efansyah, Taufik; Andaryuni, Lilik (Attractive : Innovative Education Journal, 2024)
This research examines the philosophical values ??of the tradition of sowing yellow rice in the wedding procession in the customs of the Banjar tribe from an Islamic perspective. The research method used is normative-empirical with a qualitative approach. People believe that sprinkling yellow rice on the bride and groom is a symbol of good luck and success. The philosophy of the yellow rice throwing procession at this wedding aims to; firstly, so that the bride and groom get sufficient sustenance, secondly, they become a married couple who respect each other, thirdly they avoid temptation/repulsion, fourthly they can run their household well. When viewed from the perspective of the implementation procession and the rules regarding applicable procedures, this tradition actually has a positive purpose for the newly married bride and groom. Not only the bride and groom, but also for all related parties, family, relatives and society in general. So this tradition continues continuously in every wedding procession Keywords: Philosophical Values Tradition, Tradition of Sowing Yellow Rice